Feasibility Study on Improving of Helicopter Forward Flight Speed via Modification of the Blade Dimension and Engine Performance - Nik Mohd., Nik Ahmad Ridhwan; Wahab, A. A. (2006)
The purpose of this paper is to study the feasibility on improving a 5-seaterr helicopter forward flight speed via applying the different combination between rotor and engine. The emphasis of this study is given to the increment in the main rotor number of blade from 3 to 4 blades and blade sizing at which to meet the better forward flight speed than the existing rotor design. The performance of the helicopter and the aerodynamic of rotor at steady and level flight was analysed by using the closed-form equation derived from the blade element theory (BET). The improvements in forward flight speed performance for every rotor-engine combinations were examined and detail documented in this paper. The percentage of improvements then was compared with the existing rotor data obtained from the helicopter flight manual and found that they were in good agreement.